The Role of the Sub Directorate of Cyber Crime, Ditreskrimsus in Investigating Crime of Cyber Crime - Agus Supriadi (Law Development Journal, 2020)
Cybercrime This is understandable given the inherent characteristics of cybercrime, which are cross national boundaries. Indonesia has established a regulation on cyber crime in the Law on Electronic Information and Transactions (UU ITE). This writing aims to identify and analyze the roles and constraints of the sub-directorate for cyber crime in the investigation of cyber crime.The approach method used by the author in this study is a sociological juridical approach. The research specification uses descriptive analysis, data sources come from primary and secondary data. This writing discussion is analyzed using legal certainty theory and social control theory.The role of the subdit cyber crime in conducting cyber crime investigations is to carry out investigations and investigations into special crimes (cyber) that occur in the form of summons, examinations, seizures, searches and arrests and detentions related to cyber cases being handled as well as providing assistance in the handling of cyber crime cases that are currently being handled. handled by Regional ranks / Polres. The constraints of the sub-directorate for cyber crime in the investigation of cyber crime include: the data reported by the reporter is very minimal, it is easy to remove traces of the perpetrator, the lack of evidence for investigations, my human resources are still limited and special tools to support the investigation process, the arrest of suspects we often do not can determine exactly who did it.Keywords: Cyber Crime, Role, Investigation.